2018
DOI: 10.1371/journal.pntd.0007022
|View full text |Cite
|
Sign up to set email alerts
|

Widespread circulation of West Nile virus, but not Zika virus in southern Iran

Abstract: West Nile virus (WNV) and Zika virus (ZIKV) are mosquito-borne viral infections. Over the past few decades, WNV has been associated with several outbreaks involving high numbers of neuroinvasive diseases among humans. The recent re-emergence of ZIKV has been associated with congenital malformation and also with Guillain–Barre syndrome in adults. The geographic range of arthropod-borne viruses has been rapidly increasing in recent years. The objectives of this study were to determine the presence of IgG specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…Recent investigations have detected field-collected Cx. pipiens mosquitoes, infected with WNV in Iran [9,18]. However, despite many other signs of WNV circulation based on serological and molecular detections in humans, horses, birds, and mosquitoes, the vector competence of this species remains unknown in the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations have detected field-collected Cx. pipiens mosquitoes, infected with WNV in Iran [9,18]. However, despite many other signs of WNV circulation based on serological and molecular detections in humans, horses, birds, and mosquitoes, the vector competence of this species remains unknown in the country.…”
Section: Discussionmentioning
confidence: 99%
“…as the main WNV vector [24], humans, horses, and birds, confirmed the presence of the virus in the country [25]. There is much serological and molecular evidence of WNV circulation in vectors, animal reservoirs, and dead end hosts in Iran [9,17,18,[26][27][28][29][30]. Nevertheless, only few studies have succeeded in identifying the WNV lineages circulating in the country [15,17,18]: Cx.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mosquitoes of the main genera, Culex and Aedes are incriminated as the most important vectors of arboviruses [5,6]. The increasing volume of people displacements including movements of refugees, and the traffic of goods and animals between countries of the region, offer multiple opportunities for arbovirus introduction in Iran such as dengue virus (DENV), and West Nile virus (WNV) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chinikar et al, in 2012 and 2013, found that three patients developing encephalitis were positive for WNV by RT-qPCR assay [14] and detected serologically positive sera in 1.3% of humans and 2.8% of equines [15]. WNV was also detected in mosquitoes: Aedes caspius in the Northwest [16], and Culex pipiens in the North [17] and the South [8]. Besides, the most critical mosquito-borne virus in the world is DENV mainly transmitted between humans by Aedes mosquitoes [18].…”
Section: Introductionmentioning
confidence: 99%